Bis-Lactam Peptide [i, i+4]-Stapling with α-Methylated Thialysines - Bo Wu; Weiping Zheng (Molecules, 2020)
Four bis-lactam [i, i+4]-stapled peptides with d- or l-α-methyl-thialysines were constructed on a model peptide sequence derived from p110α[E545K] and subjected to circular dichroism (CD) and proteolytic stability assessment, alongside the corresponding bis-lactam [i, i+4]-stapled peptide with l-thialysine. The % α-helicity values of these four stapled peptides were found to be largely comparable to each other yet greater than that of the stapled peptide with l-thialysine. An l-α-methyl-thialysine-stapled peptide built on a model peptide sequence derived from ribonuclease A (RNase A) was also found to exhibit a greater % α-helicity than its l-thialysine-stapled counterpart. Moreover, a greater proteolytic stability was demonstrated for the l-α-methyl-thialysine-stapled p110α[E545K] and RNase A peptides than that of their respective l-thialysine-stapled counterparts.